Pendampingan Pengenalan IoT dalam Pertanian Pintar : Strategi Meningkatkan Produktivitas Tani di Desa Jurit Kabupaten Lombok Timur - Juliansyah, Akbar; Mulada, Diman Ade; Purmadi, Ary (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to empower farmer groups in Jurit Village, East Lombok Regency, through the introduction of smart farming technology based on the Internet of Things (IoT). The initiative seeks to enhance agricultural productivity and economic empowerment by integrating advanced technology with robust business legalities. The participatory method employed in this program is based on the four-dimensional approach: Purpose, Process, Partnership, and Product. The outcomes of this community service demonstrate an improvement in the understanding and capabilities of the Lombok Organik farmer group in implementing IoT-based smart farming technology. Furthermore, the farmer group successfully established a legally recognized business, enabling them to expand market access and improve the competitiveness of their agricultural products.